Incidencia del costo de ventas en la rentabilidad de Reybanpac C.A. de la ciudad de Guayaquil, periodo 2023. - Samaniego Samaniego, Karen Vanessa (2024)
The main objective of this research was to analyze how the cost of sales impacts the profitability of Reybanpac C.A. during the 2023 period. To achieve this, inductive and deductive methods were employed, combining quantitative and qualitative approaches. The quantitative method allowed for the collection and analysis of financial data related to costs and profits, while the qualitative approach provided insights into internal factors such as policies and business strategies. Techniques used included document analysis of financial records and structured interviews with the company’s manager, ensuring a comprehensive and robust approach. The results showed that efficient management of the cost of sales has a direct impact on profitability. It was evident that months with significant cost increases resulted in lower profit margins. From the qualitative analysis, internal issues such as inefficient planning and limited control of inputs were identified as contributors to cost increases. In conclusion, the profitability of Reybanpac C.A. largely depends on effective cost management. It is recommended to strengthen financial planning, improve operational processes, and renegotiate agreements with suppliers. These actions will optimize profitability and ensure sustainable growth for the company in the future.